Comparison of the "Tall and Fall" Versus "Drop and Drive" Pitching Styles: Analysis of Major League Baseball Pitchers During a Single Season. Issue 5 (19th May 2023) - Beaudry, Mason F.; Beaudry, Anna G.; Bradley, James P.; Haynes, David E.; Holland, Glenn; Edwards, Audrene; Baker, Brent A.; Jacobson, Bradley R.; Chetlin, Robert D.
Background: Previous research has documented the proportion of "tall and fall" (TF) and "drop and drive" (DD) pitching styles among Major League Baseball (MLB) pitchers who underwent ulnar collateral ligament reconstruction (UCLR). The proportion of these 2 styles among all MLB pitchers remains unknown. Purpose: To determine the proportion of the TF and DD pitching styles in all rostered MLB pitchers during a single season as well as the proportion of TF and DD pitchers who sustained an upper extremity (UE) injury and those who underwent UCLR. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Pitcher demographic characteristics from the 2019 MLB season and pitching information were obtained via open-access sources. Two-dimensional video analysis was used to categorize the included pitchers into TF and DD groups. Statistical comparisons and contrasts were made using 2-tailed t tests, chi-square tests, and Pearson correlation analyses as appropriate. Results: Of the 660 MLB rostered pitchers in 2019 (age, 27.39 ± 3.51 years; body mass index, 26.34 ± 2.47 kg/m 2 ; fastball velocity, 150.49 ± 3.99 kph [93.51 ± 2.48 mph]), 412 (62.4%) pitchers used the TF style and 248 (37.6%) pitchers used the DD style. Significantly more UE injuries were seen in the TF group compared with the DD group (112 vs 38 injuries, respectively; P < .001). Twelve pitchers underwent UCLR (TF, 10; DD, 2), representing a 1.8% UCLR rate among all pitchers. This was a second surgery for 2 pitchers, both of whom used the TF pitching style. Significantly more pitchers in the TF group than the DD group had undergone UCLR before 2019 (135 vs 56 pitchers, respectively; P = .005). Conclusion: The results of the present study demonstrated a higher prevalence of both UE injury and prior UCLR in TF pitchers. Further research is needed to explore the potential association between pitching style and UE injury.